2021
DOI: 10.1113/jp281845
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping heart failure using model‐based analysis and physiology‐informed machine learning

Abstract: support-information-section).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 45 publications
5
22
0
Order By: Relevance
“…Using the unsupervised machine learning method from Jones et al. (2021), convex hulls of the four disease groups were created, and the subjects were clustered into two groups to account for one hypothetically more healthy and one hypothetically more diseased group. Before the PCA and clustering were applied, the parameters were standardized by centring and dividing each parameter value by the SD of that parameter.…”
Section: Methodsmentioning
confidence: 99%
“…Using the unsupervised machine learning method from Jones et al. (2021), convex hulls of the four disease groups were created, and the subjects were clustered into two groups to account for one hypothetically more healthy and one hypothetically more diseased group. Before the PCA and clustering were applied, the parameters were standardized by centring and dividing each parameter value by the SD of that parameter.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have identified subgroups of patients with distinct phenotypes of HFpEF based on their profiles and outcomes using unsupervised clustering algorithms (Table 4). 6,[45][46][47][48][49][50][51][52][53][54] Across the studies, types of clustering used primarily are hierarchical, K-means, and density based (Figure 2). Hierarchical agglomerative clustering is a bottom-up approach such that each data point begins in a separate cluster, and pairs of clusters at the bottom are merged going up the hierarchy.…”
Section: Phenomappingmentioning
confidence: 99%
“…Several studies have identified subgroups of patients with distinct phenotypes of HFpEF based on their profiles and outcomes using unsupervised clustering algorithms ( Table 4 ). 6,45–54 Across the studies, types of clustering used primarily are hierarchical, K‐means, and density based ( Figure ).…”
Section: Applications Of Artificial Intelligence In Heart Failurementioning
confidence: 99%
“…6 Prior studies have succeeded in stratifying HFpEF into several phenotypes in multiple cohorts that included a small number of Asian but not Japanese patients. [7][8][9][10][11][12] The distribution of patient population characteristics was significantly different between Western and Eastern countries, especially in terms of mean body mass index (BMI) and the incidence of obesity. In the recent HFpEF worldwide registry, the Asian patient population demonstrated lower BMI, a frequent incidence of atrial fibrillation (AF), poor kidney function, and a history of HF admission.…”
Section: Introductionmentioning
confidence: 99%